Hypnosis and Hypnotic ability between old beliefs and new evidences: An epistemological reflection. Issue 1 (15th October 2021) - Facco, Enrico
ABSTRACT: The history of hypnosis has been marked by its effectiveness paralleled by prejudicial refusal, due to its ostensible incompatibility with the ruling Weltbild (picture of the world). Its interpretation has been mainly based on concepts like suggestibility, dissociation, hallucination, impairment of sense of agency, and free will. Nevertheless, little evidence and agreement has been reached so far on the nature of hypnosis and hypnotic ability, an uncertainty enhanced by the wide range of meanings and ambiguities of the used terms. This article analyzes the main epistemological implications involved in the topic.